Effect of Occlusal Reduction on Postoperative Pain during Root Canal Treatment in Teeth with Symptomatic Apical Periodontitis (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Pain management after root canal treatment is a very important issue in clinical practice. Occlusal reduction has been widely used after root canal treatment to reduce post treatment pain and flare up. The purpose of this study was to evaluate the effect of occlusal reduction on postoperative pain in teeth with symptomatic apical periodontitis.MATERIALS AND METHODS: Seventy mandibular molar teeth with symptomatic apical periodontitis requiring root canal treatment were included in this study. Each patient who met the inclusion criteria had a serial number allocated, ranging from 1 to 70. The patients were divided into two groups i.e, occlusal reduction group and without occlusal reduction group according to the odd and even numbers on the list. After administration of local anesthesia, the root canals were instrumented, and an intracanal calcium hydroxide dressing was placed. Following confirmation with articulating paper, occlusal reduction group received a 2 mm reduction in occlusal contacts. Preoperative pain before start of the procedure and postoperative pain 6 days after instrumentation were recorded on visual analogue scale. Data was evaluated by chi-square test and Man Whitney U test with p-value 0.05) after root canal preparation. CONCLUSIONS: Occlusal surface reduction did not provide any further reduction in postoperative pain for teeth with symptomatic apical periodontitis compared with no occlusal reduction